Factors influencing attrition among learners : Faculty of Applied Social Sciences in OUM - Noor Hassline Mohamed; Noor Zuleika Zulkipli (2014)
This study examined factors affecting the attrition rate among learners in Open and Distance Learning (ODL) institution. The main focus of the study is to explore what factors cause the attrition, and what are the best ways or strategies to prevent the attrition rate among adult learners. There were 15 adult learners from the Faculty of Applied and Social Sciences (FASS) at Open University Malaysia (OUM) were taken from the population of dormant learners which were not registered for three concurrent semesters. The study found that the main factor of attrition was learners were overextended with too many responsibilities. The three ways to prevent attrition among learners were learners’ communication, learners’ mentoring, and learners’ awareness. It is recommended that the best practice for prevention learners’ attrition was learner itself. This study offered two benefits, factors affecting the attrition rate among adult learners and offered some ways in preventing attrition among adult learners from learners’ own perspective. Therefore, this study can be used as a benchmark for the faculty to handle the attrition cases for adult learners in open and distance learning institutions. (Abstract by author)